lnfluência da prática pedagógica na mudança conceptual em ciências: um estudo sociológico - Margarida Afonso; Isabel Neves Pestana (Universidade do Minho, 2000)
The study analyses the influence of two distinct pedagogic practices on science conceptual change by socially differentiated children. Bernstein theory of pedagogic discourse is used to characterize pedagogic practices and to analyse poduction of the legitimate text. The sample was made up of 57 students of the 5 year of schooling. Water´s evaporation and condensation were the scientific concepts studied. The results suggest that students´ conceptual change, particularly of the disadvantaged, is facilitated by a pedagogic practice which makes explicit the text to be produced by the students, which gives some control to students in the pedagogic interaction and which makes relations between knowledges (particularly, academic non academic). Such a practice is also more effective in changing the concepts more resistant to change. The study suggests that the conceptual change is the result of the greater efficiency of the practice to lead students to acquire recognition and/or realization rules for the scientific contexts studied.